Endophytic colonisation of tobacco, corn, wheat and soybeans by the fungal entomopathogen Beauveria bassiana (Ascomycota, Hypocreales) - Russo, M.L. (2015)
We demonstrate the effectiveness of three inoculation methods (foliar spray, seed immersion and root immersion) in establishing fungal the entomopathogen Beauveria bassiana as an endophyte in tobacco, corn, wheat and soybean. Colonisation of leaves by B. bassiana was assessed 7, 14, 21 and 28 days postinoculation. There were significant differences (p < 0.001)in endophytic colonisation among the different inoculation techniques.